Innovative agrifood supply chain network: Leading to traditional, "back to the future" foods - Paraskevi Christina Sakali; Dimitris Skalkos (International Journal of Business Science & Applied Management (IJBSAM), 2016)
The agrifood sector is faced with major challenges that arise from changes in the sector's economic and non- economic environments, to changes in consumers' lifestyles, from global increases in food consumption, to diminishing production base and now days from the not stable political and economic situation and the continuous global economic deceleration of growth. The challenges cannot be met by any individual enterprise but it requires concerted actions and coordination of initiatives within an effective food chain management. By utilizing basic concepts of innovation management techniques (IMTs), and developing an innovative management (M.I.) process we have applied innovation in two enterprises of the same traditional food chain for a three year period and evaluated the results based on the 12 different parameters developed by the innovation radar. The results show that the applied methodology had a major impact to the growth of both companies and the upgrade of their innovation capacity. In terms of the impact of the methodology within the food chain itself the success is evaluated based on the new, innovative, "BACK TO THE FUTURE" foods which were developed and promoted in the market by these companies and their close collaboration. Thus, we have developed a useful and valuable innovation practical tool available to managers of companies and to policy makers which can be used effectively for local development and regional growth of the agri food sector. Further research applying the methodology in agri food chains of other sectors such as dairy, meat etc., in bigger companies in the traditional and non-traditional sector is required in order to better evaluate its validity and effectiveness.
Keywords: 650; food supply chain; agrifood; innovation; Innovation management techniques; back to the future foods